Rural Aquaculture 2002
DOI: 10.1079/9780851995656.0143
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable development of floating net cage culture for income security in rural Indonesia: a case study of common carp production at Lake Maninjau, Indonesia.

Abstract: Commercial floating net cage culture is a rapidly growing industry in rural Indonesia. It has become the economic base for income generation in poverty alleviation programmes of the government of West Sumatra province in two villages at Lake Maninjau. The increasing interest in cage development raises questions of its determining factors. This study investigated the influence of different factors on common carp production in cages at Lake Maninjau. Although production function analysis showed that higher fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In Vietnam, fish are raised on agricultural waste products such as rice hulls; this practice is also used in the Philippines (Pekar et al 2002;Prein et al 2002). Cage aquaculture is also employed in the lakes and rivers of Indonesia (Munzir and Heidhues 2002) and China (Lu 1992). Because fish protein is affordable and easy to grow, many of the world's people depend heavily on freshwater fisheries.…”
Section: Socioeconomic Effectsmentioning
confidence: 99%
“…In Vietnam, fish are raised on agricultural waste products such as rice hulls; this practice is also used in the Philippines (Pekar et al 2002;Prein et al 2002). Cage aquaculture is also employed in the lakes and rivers of Indonesia (Munzir and Heidhues 2002) and China (Lu 1992). Because fish protein is affordable and easy to grow, many of the world's people depend heavily on freshwater fisheries.…”
Section: Socioeconomic Effectsmentioning
confidence: 99%
“…Early research on technical efficiency (TE) in agriculture focused on crop and animal industries; these studies used cross‐sectional data, panel or aggregate data, the production function, the parametric or nonparametric boundary function, and mathematical programming as analytical approaches (Chennareddy ; Sahota ; Lau and Yotopoulos ; Sidhu ; Kumbhakar ; Papadas and Dahl ; Gow and Langemeier ; Alvarez and Arias ; Hoang and Alauddin ). In recent years, the majority of the efficiency studies have centered on TE analysis in aquaculture production (Sharma and Leung ; Sharma ; Sharma et al ; Dey et al ; Munzir and Heidhues ; Icebalcata and Lavergne ; Kaliba and Engle ; Ogundari and Akinbogun ; Huang ); however, these models are seldom used to research cost or economic efficiency. Therefore, Iliyasu et al () suggested that future research should estimate all three efficiency indices (i.e., TE, allocative efficiency [AE], and economic efficiency).…”
mentioning
confidence: 99%